Natural isothiocyanates express antimicrobial activity against developing and mature biofilms of Pseudomonas aeruginosa - Kaiser, Stefan J.; Mutters, Nico T.; Blessing, Brigitte; Günther, Frank (Fitoterapia, 2017)
Background: The antimicrobial properties of natural isothiocyanates (ITCs) found in plants such as nasturtium (Tropaeolum majus) and horseradish (Armoracia rusticana), and the need of new chemotherapeutic options for treatment of infections caused by multidrug-resistant and biofilm-forming Gram-negative bacteria such as Pseudomonas aeruginosa (Pa), led us to evaluate the effects of three major ITCs, allylisothiocyanate (AITC), benzylisothiocyanate (BITC), and phenylethyl-isothiocyanate (PEITC), and a mixture (ITCM) adapted to the ITC composition after release of active components out of natural sources.Material/methods: Out of 105Pa isolates 27 isolates with increased biofilm formation were selected for testing. The effects of ITCs on Pa were evaluated regarding (1) planktonic bacterial proliferation, (2) biofilm formation, (3) metabolic activity in mature biofilms, and (4) synergism of ITCs and antibiotics. Results:(1) Each ITC had anti-Pa activity. Mean minimum inhibitory concentrations (MICs) were (μg/ml, mean±standard deviation): AITC 103±6.9; BITC, 2145±249; PEITC 29,423±1652; and ITCM, 140±5. (2) Treating bacteria with PEITC and ITCM in concentrations below the MIC significantly inhibited biofilm formation. Particularly, ITCM reduced biofilm mass and bacterial proliferation. (3) ITCs significantly inhibited metabolic activity in mature biofilms. (4) Combining ITCs with meropenem synergistically increased antimicrobial efficacy on Pa biofilms. Conclusions: ITCs represent a promising group of natural anti-infective compounds with activity against Pa biofilms.
Gesehen am 14.07.2018